The Impact of Co-Curricular Method on Students’ Character Education in Higher Education - Narwikant Indroasyoko; Achmad Muhammad; Nia Nuryanti Permata (Politeknik Negeri Bali, 2020)
Abstrac : The assessed co-curricular can build students’ character. However, the study which describe about it has not existed until now. The aim of this study is to acquire deep knowledge about co-curricular program as method in character education, so the concept and strategy to operate it efficiently and effectively can be obtained. Data is collected by using questionnaire instrument of Social Skill Improvement System Rating Scale or SSIS-RS (Gresham & Elliot, 2008) distributed to students who participate in co-curricular from various fields, in which 131 students become sample. The data result is analyzed by using factor analysis technique to find out which factor is dominant and to determine variable rank. The study result shows that co-curricular participant students can build their character by 68%, specifically, character education with co-curricular in field of sports is 76%, arts is 60%, and special skill is 65%, and the rest is stimulated by other factors which had not been revealed. It can be concluded that sports in co-curricular activity give the most dominant contribution in forming students’ character compared with another field